The Interplay of the Gut Microbiome, Bile Acids, and Volatile Organic Compounds - Nidhi M. Sagar; Ian A. Cree; James A. Covington; Ramesh P. Arasaradnam (Gastroenterology Research and Practice)
Background. There has been an increasing interest in the use of volatile organic compounds (VOCs) as potential surrogate markers of gut dysbiosis in gastrointestinal disease. Gut dysbiosis occurs when pathological imbalances in gut bacterial colonies precipitate disease and has been linked to the dysmetabolism of bile acids (BA) in the gut. BA metabolites as a result of microbial transformations act as signaling molecules and have demonstrated regulation of intestinal homeostasis through the TGR5 and FXR receptors by inhibiting inflammation, preventing pathogen invasion, and maintaining cell integrity. The presence of VOC footprints is the resultant effect to gut microbiome substrate fermentation. Aim. To review the role of the gut microbiome and bile acid signaling in intestinal homeostasis and the resultant use of VOCs as potential noninvasive surrogate biomarkers in gut dysbiosis. Methods. A systematic search on PubMed and Medline databases was performed to identify articles relevant to gut dysbiosis, BA metabolism, and VOCs. Conclusions. The host and presence of the gut microbiome appear to regulate the BA pool size. A dysbiotic gut microbiome results in disrupted intestinal homeostasis, which may be reflected by VOCs, differentiating those who are healthy and those with disease.